2020
DOI: 10.1111/1750-3841.15128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing consumers’ understanding of the term “Natural” on food labeling

Abstract: The objective of this study was to gain a better understanding of how consumers’ interpret the term “natural” by assessing food choice based on labels describing attributes of a product associated with the term “natural”; to assess food intake of chosen food, and; to determine factors that influence food choice and intake. A randomized, single‐visit pilot study was conducted where participants (n = 105) were presented with seven identical bowls of granola each bearing a different descriptive label. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The nutritional claim "natural" appeared on the labels of three smoothies (type F) and one smoothie (type FC). Some authors have studied consumers' interpretations regarding the food label term "natural", with further examination and support that cognitive choices are aligned with food intake behavior [57]. Most of the consumers in that study associated the term "natural" with: "no preservatives", "organic" and "made with real ingredients".…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional claim "natural" appeared on the labels of three smoothies (type F) and one smoothie (type FC). Some authors have studied consumers' interpretations regarding the food label term "natural", with further examination and support that cognitive choices are aligned with food intake behavior [57]. Most of the consumers in that study associated the term "natural" with: "no preservatives", "organic" and "made with real ingredients".…”
Section: Discussionmentioning
confidence: 99%
“…To add to this confusion, several studies concluded that the terms natural and organic were highly related as well and may even be perceived as identical (Amos et al., 2019; Kuchler et al., 2020; Rahman et al., 2020).…”
Section: Limitations Of CL As a Heuristic For Food Choicementioning
confidence: 99%